Development of CO2 Emission Factors and Evaluation of Emissions from Municipal Solid Waste Incineration Facility - Chung, Jindo; Jung, Insu; Song, Jangheon (Asian Journal of Chemistry, 2013)
In order to cope actively with the international environmental norms for the reduction of greenhouse gas emissions, it is required to estimate the national greenhouse gas emissions and develop country-specific greenhouse gas emission factor. In order to secure more accurate statistics of CO2 emission from incineration facilities of the country's municipal solid wastes, this study compared and analyzed Tier 2a method applying the emission factor presented in the 2006 IPCC Guideline, Tier 3 method using the facility's characteristic value and CO2 emission provided based on the actual measurement. The average Tier 2a CO2 emission based on the Tier 2a method is 25,310tCO2 eq/yr while that provided based on the Tier 3 method is 43,901tCO2eq/yr, which suggests that the former is underestimated by 42% compared to the Tier 3 method. Comparing with the average CO2 emission based on actual measurement, 36,269CO2eq/yr, the estimate based on the Tier 2a method is 25,310CO2 eq/yr, underestimated by 43 % compared with that provided based on actual measurement while the estimate generated from the Tier 3 method is 43,901CO2 eq/yr, overestimated by 21 % compared with that from actual measurement. This difference comes from the fact that the estimate from the Tier 2a method is based on the basic value presented in the IPCC Guideline and that the difference between the Tier 3 method using the facility's unique material and the estimate from actual measurement comes from the consideration of composition of wastes, contents of dry substances, carbon contents in fossil fuels and variables affecting oxidation factors. Further study is still needed to determine accurate CO2 emission rates from municipal solid waste incineration facilities and other various combustion facilities by obtaining country-specific emission factor, rather than relying on IPCC default emission factor. This study included the results of utilizing the waste characteristic values of single municipal solid waste incineration facilities. In the future, it is required to do continuous research and development on the estimation of CO2 emissions and emission factors for various incineration facilities for the development of country-specific emission factors.